Anti-Oppressive Practice and Reflexive Lifeworld-Led Approaches to Care: A Framework for Teaching Nurses about Social Justice - Jacqueline Sarah Hutchison (Nursing Research and Practice)
This paper was initially written for a European Academy of Caring Science workshop and aimed to provide clarity and direction about Caring Science by offering some ideas emerging from the philosophy, themes, and projects of EACS. An underpinning concept for the work of the Academy is the lifeworld. The focus of the workshop was to explore the lifeworld of the patient, student, and carer. The intention was to promote discussion around the need to provide alternative ways to conceptualise caring relevant knowledge, naming phenomena and practices central to caring sciences, and the educational curriculum and its adequacy for caring science. This paper seeks to identify concepts and approaches to understanding oppression, power, and justice which enable nurses to challenge the structures in health care environments which discriminate or disempower clients. Anti-oppressive practice theory and reflexive lifeworld-led approaches to care enable nurses to be critical of their practice. A framework for teaching social justice in health care is offered to augment teaching students to challenge oppressive practice and to assist nurses to reflect and develop conceptual models to guide practices which are central to promoting caring interactions.